BANK LIQUIDITY: THE RELEVANCE OF COMMERCIAL LOAN THEORY IN THE CONTEXT OF INDONESIAN BANKING INSTITUTIONS - Nur Anita; Muhammad Khafid; Niswah Baroroh (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2025)
This study investigates the effect of leverage, profitability, and firm size on the liquidity of banking firms listed on the Indonesia Stock Exchange (IDX), with particular attention to the moderating role of firm size. This study uses a quantitative approach. The population of this study is banking companies listed on the Indonesia Stock Exchange from 2020 to 2024. The sampling technique uses purposive sampling, which produces a sample of 235 analysis units. Data collection in this study uses documentation techniques. Data analysis uses panel data regression and moderated regression analysis (MRA). The findings reveal that leverage significantly negatively affects liquidity, supporting the principles of Commercial Loan Theory, which emphasizes maintaining liquidity through short-term, self-liquidating assets. The results demonstrate that firm size significantly enhances liquidity, while profitability shows no significant direct effect. Moreover, firm size moderates the relationship between leverage and liquidity in a positive direction, suggesting that larger banks can better withstand the liquidity risks associated with high leverage. Conversely, firm size negatively moderates the relationship between profitability and liquidity, implying that larger banks may reinvest profits into long-term, less liquid assets. This study contributes to the financial management literature by revisiting the relevance of Commercial Loan Theory in the context of Indonesian banking institutions. By integrating firm size as a moderating variable, the research offers a novel perspective on how internal firm characteristics influence the relationship between financial structure and liquidity. Furthermore, using the quick ratio to measure bank liquidity introduces a conservative and less common approach in banking studies, enriching the methodological diversity in liquidity research.